2021
DOI: 10.3390/coatings11080908
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Strontium Substituted Calcium Phosphate Coating for Bone Regeneration

Abstract: Cellulose acetate (CA)/strontium phosphate (SrP) hybrid coating has been proposed as an effective strategy to build up novel bone-like structures for bone healing since CA is soluble in most organic solvents. Strontium (Sr2+) has been reported as a potential agent to treat degenerative bone diseases due to its osteopromotive and antibacterial effects. Herein, bioactive hybrid composite SrP-based coatings (CASrP) were successfully produced for the first time. CASrP was synthesized via a modified biomimetic meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…118 BC is a bacterial extracellular wall product of Gluconacetobacter xylinus that has been grown in a liquid sugar matrix and has a structure similar to that of ECM components. 119,120 Previous studies have demonstrated the application of BC for bone healing, 121 wound healing, 122 and ophthalmic scaffolds. 120 This study further verified through in vivo and vitro experiments that the prepared functionalized Ti had favorable biocompatibility and excellent osteogenic properties (Figure 8C), and that G. xylinus initiates a detoxification mechanism in the presence of excess metal ions to avoid their biotoxicity.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…118 BC is a bacterial extracellular wall product of Gluconacetobacter xylinus that has been grown in a liquid sugar matrix and has a structure similar to that of ECM components. 119,120 Previous studies have demonstrated the application of BC for bone healing, 121 wound healing, 122 and ophthalmic scaffolds. 120 This study further verified through in vivo and vitro experiments that the prepared functionalized Ti had favorable biocompatibility and excellent osteogenic properties (Figure 8C), and that G. xylinus initiates a detoxification mechanism in the presence of excess metal ions to avoid their biotoxicity.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%